2003
DOI: 10.1007/s00268-002-6569-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surgical Treatments of Gallstone Ileus: Preliminary Report

Abstract: Gallstone ileus is an uncommon cause of small bowel obstruction, accounting for only 1% to 4% of all intestinal obstructions. In the group of patients over 65 years of age, gallstones cause about 25% of all non-strangulated obstructions of the small bowel. Gallstone ileus is burdened with high mortality rate, ranging from 12% to 18%, and most patients are of advanced age, with many other concomitant diseases that may increase the operative risk. The purpose of this study was to compare the two investigated sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
0
13

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 8 publications
3
106
0
13
Order By: Relevance
“…22 ASA scores were similar between the two groups but operating times were significantly longer for the one-stage procedure. Logistic regression analysis showed that only urgent fistula repair was significantly associated with postoperative complications.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…22 ASA scores were similar between the two groups but operating times were significantly longer for the one-stage procedure. Logistic regression analysis showed that only urgent fistula repair was significantly associated with postoperative complications.…”
Section: Resultsmentioning
confidence: 78%
“…Logistic regression analysis showed that only urgent fistula repair was significantly associated with postoperative complications. 22 The authors concluded that enterolithotomy is the procedure of choice, with a one-stage procedure reserved for patients with acute cholecystitis, gallbladder gangrene or residual stones. 22 However, the study was not randomised and the selection process for each operative approach was not detailed; it is likely that there was selection bias for the two operative approaches.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plain abdominal X-ray could visualize air-fluid level in 77.8%, bowel loop dilatation in 88.9%, pneumobilia in 37%, air in gallbladder in 3.7% and ectopic stone in 33% of patients according to the clinical study conducted in Italy [11]. Helical CT may improve the diagnosis of gallstone ileus providing important information [12,13]. Abdominal ultrasound may also prove to be a useful tool for the diagnosis [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…A spontaneous closure of the fistulous tract is observed in more than 50% of cases. 10,13 Recently, laparoscopy assisted enterolithotomy and endoscopic removal are becoming the preferred approaches for the treatment of GI. 14,16 Delayed diagnosis, concomitant comorbidity and advanced age are the causes of a high mortality rate (7.5-15%).…”
Section: -6mentioning
confidence: 99%